The Representation of Character Education Values in Aris Kurniawan’s Short Story “Tiga Cita-Cita Kasmin”: A Mimetic Approach - Sugiyo Sugiyo (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Despite the growing number of studies on literary works and character education, limited research has specifically examined how social reality in contemporary Indonesian short stories reflects character education values through a mimetic perspective. This gap highlights the need to explore the relationship between literary representation and educational values in a more focused textual context. The novelty of this study lies in its integration of the mimetic approach with character education analysis in Aris Kurniawan’s short story “Tiga Cita-Cita Kasmin.” This study aims to describe the representation of the protagonist’s life reality and the values of character education in the short story “Tiga Cita-Cita Kasmin” by Aris Kurniawan using a mimetic approach. This research employed a descriptive qualitative method, with the short story serving as the primary data source. Data were collected through reading and note-taking techniques, while data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the short story represents the reality of lower-class rural community life through Kasmin’s experiences within the family, society, Islamic boarding school, and literary community. This representation embodies dominant character education values, including simplicity, gratitude, modesty, love and affection, adaptability, social awareness, creativity, empathy, religiosity, discipline, hard work, responsibility, honesty, curiosity, appreciation of achievement, self-confidence, and perseverance. Theoretically, this study confirms that the mimetic approach remains relevant for uncovering the relationship between social reality and character education values in literary works. Practically, the short story has strong potential to be used as teaching material in literature learning and character education. However, this study is limited to a single short story and has not examined its classroom implementation; therefore, further studies are recommended to conduct comparative analyses and classroom-based implementation testing.